Papel dos receptores vaniloides TRPV1 da matéria cinzenta periaquedutal na ansiedade e na antinocicepção induzida pelo medo em camundongos - Mascarenhas, Diego Cardozo (Universidade Federal de São Carlos, 2013)
When confronted with fear situations rodents exhibit behavioral (e.g., fight, flight, immobility and vocalization) and neurovegetative (tachycardia, hypertension and defecation) responses that characterize the defense reactions. In general, these responses are accompanied by antinociception. The exposure of animals to the paradigm of the Elevated Plus Maze (EPM) results in a repertoire of defensive responses and antinociception, since the open arms of the EPM represents a threat to rodents. Several studies have investigated the neural substrate involved in the neurotransmission and neurobiology of aversive situations-induced antinociception, and many have highlighted the involvement of the dorsal portion of periaqueductal gray matter (dPAG). Several mediators which play an important role in modulation of fear/anxiety and nociception states, has been studied and, recently, with the discovery of TRPV1 receptor (Transient Receptor Potential vanilloid type-1), vanilloid compounds, which are agonists of this ion channel, are gaining prominence. It is unclear the role played by these compounds in the modulation of these emotions, since there are some conflicting results in the literature regarding its effects. However, through the use of genetic and pharmacological tools, the vanilloid compounds appear as an interesting target in an attempt to elucidate the neurobiology of pain and anxiety. Thus, the present study aimed to investigate the role of these vanilloid compounds in the modulation of fear/anxiety as well as aversive environment-induced antinociception. Animals were submitted to the agonist capsaicin microinjection intra-dPAG (0, 0.01, 0.1 or 1 nmol) which in the dose of 1 nmol reduced nociception assessed by the formalin test, and increased anxiety assessed by EPM test. Antagonist capsazepine microinjection intra-dPAG (0, 10, 30 or 60 nmol) did not cause any effect on anxiety assessed by EPM. However, the dose of 60 nmol mimicked the capsaicin effects, promoting antinociception assessed by the formalin test, suggesting a tonic role of vanilloids in pain. Interestingly, it was demonstrated the TRPV1 receptor specificity, since mice submitted to capsazepine prior treatment intra-dPAG at dose devoid of effect per se effect (30 nmol) in anxiety and nociception, had the pro-aversive and antinociceptive capsaicin effect completely and selectively reversed. Finally, this same capsazepine dose (30 nmol) was able to attenuate the aversive environment-induced antinociception elicited by the fully open EPM (oEPM: four open arms). Altogether, our results suggest an important role played by the vanilloid compounds in the modulation of defense reactions and antinociception. Also, the pro-aversive and antinociceptive effects of capsaicin are primarily due to selective activation of TRPV1, and finally, the antagonist capsazepine is able to attenuate the oEPM-induced antinociception, a maze derived from the EPM apparatus which elicits more aversion.
Keywords: Ansiedade; Antinocicepção; Vaniloides; Matéria cinzenta periaquedutal; Camundongos; CIENCIAS BIOLOGICAS::FISIOLOGIA